2017
DOI: 10.12799/jkachn.2017.28.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Joint Health Self-management Program for the Elderly with Knee Osteoarthritis in Communities: Applying the IMB Model

Abstract: Purpose:The purpose of this study is to develop and evaluate a joint health self-management program for knee osteoarthritis elders in communities. Methods: This program was developed based on the IMB (information-motivationbehavioral skills) model. The program methods include education, setting and achieving goals, sharing experiences, telephone counseling, and self-monitoring. The topics of the program include joint assessment, exercise, massage, joint protection, medication, depression management, diet, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Self‐efficacy improved by providing personal feedback regarding self‐management and similar experiences when using the web‐based diabetes self‐management program (Jung, ). Kim and Park () suggested that self‐monitoring is effective for promoting self‐efficacy. The method of promoting self‐efficacy varies based on previous experience with successful accomplishments, vicarious experiences, verbal persuasion, and support from others (Bandura, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐efficacy improved by providing personal feedback regarding self‐management and similar experiences when using the web‐based diabetes self‐management program (Jung, ). Kim and Park () suggested that self‐monitoring is effective for promoting self‐efficacy. The method of promoting self‐efficacy varies based on previous experience with successful accomplishments, vicarious experiences, verbal persuasion, and support from others (Bandura, ).…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by the IMB model, information regarding self‐management and personal and social motivation for self‐management improved behavioral skills and promoted behavior changes. Through information education, the enhancement of personal motivation by establishing and achieving self‐management goals, enhancement of social motivation through sharing experiences with colleagues and professional counseling, and promotion of self‐efficacy through self‐monitoring, self‐management performance was improved (Kim & Park, ). In addition, the researcher periodically analyzed program utilization and self‐management performance of the subjects using the application server.…”
Section: Discussionmentioning
confidence: 99%
“…Since health-related information directly influences exercise behavior, it is crucial to provide necessary education to workplace workers. It is advisable to develop the educational content based on literature review and preliminary survey on exerciserelated information that participants are interested in [42,43]. Personal motivation plays a crucial role in fostering exercise motivation.…”
Section: Discussionmentioning
confidence: 99%